Teachers’ views on challenges affecting learners’ performance in natural science - M.N.N. Ndjangala; J. Abah; P. Mashebe (International Journal of Evaluation and Research in Education (IJERE), 2021)
In Namibia, natural science (NS) is one of the priority subjects in upper primary phases (Grades 4 to 7). However, in the Omusati Region of Namibia, there are increasing public concerns that many learners are not performing well in NS. Thus, this study surveyed the views of NS teachers on the challenges affecting upper primary learners’ performance in NS at three selected combined schools in the Omusati Region. Qualitative research design using face-to-face interview was used to gather the views of upper primary NS teachers in the schools. Seven teachers who are currently teaching NS at the selected schools were selected using the purposive sampling method to participate in the study. The results obtained revealed that the following challenges affect upper primary learners’ performance in NS in the selected schools: medium of instruction, lack of adequate teaching and learning resources, lack of laboratories, sensitive topics, overcrowded classroom, indiscipline among learners, absenteeism, unfavorable teaching environment, hunger, and lack of proper guidance from subject advisory teachers. The study recommended that the government should provide schools with feeding programs, build laboratories, renovate classes and provide teaching materials. The schools should evolve disciplinary measures to check the learners’ indiscipline.